KARAKTERISTIK SIFAT PREBIOTIK TEPUNG DALUGA HASIL MODIFIKASI HEAT MOISTURE TREATMENT - Nestri Purnamasari; Didah Nur Faridah; Betty Sri Laksmi Jenie (Jurnal Teknologi dan Industri Pangan, 2019)
Daluga (Cyrtosperma merkusii. (Hassk.) Schott) is one of tubers originating from Siau Island, Manado, North Sulawesi. The resistant starch of daluga can be utilized as a potential source of prebiotic. However, naturally daluga has low resistant starch content and a modification is necessary for improving its content. The aim of the study was to examine the effect of heat moisture treatment (HMT) on the resistant starch content and prebiotic properties of modified daluga flour. The HMT modification was carried out at 121°C for 60 min in an autoclave, and the modified flour was then compared with the untreated native flour (TD). The results showed that autoclaved TD-HMT flour had 8.81% higher resistant starch content as compared to that of TD. The increment also affected the prebiotic characteristics of the modified flour. The TD-HMT showed resistant to gastric acid up to 92%, augmentations of prebiotic activity, index and effect, as well as  L. plantarum BSL growth improvement up to 3 log CFU/mL. The gastric acid resistant autoclaved TD-HMT is able to stimulate probiotic LAB growth, confirming its prebiotic potential for acid bacteria fermentation.